The EFL Learners’ Perceptions toward Mobile Device Usage and Mobile-Assisted Language Learning (MALL) at English Department of Mulawarman University - Aminah Rhasa Wulan; Istanti Hermagustiana (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2019)
The purposes of this study were to find English department English as foreign language (EFL) learners’ perceptions toward mobile device usage and mobile-assisted language learning (MALL), and also to find the significant correlation between English department EFL learners’ perceptions towards MALL and EFL learners’ grade point average (GPA). The survey research design was applied to get the data needed. The questionnaire was distributed to the 150 samples from the fourth and the sixth-semester students of English department of Mulawarman University. The result revealed that the mean score of EFL learners’ perceptions toward mobile device usage was 44.83, which was equal with 81.50% of learners could be categorized as positive perception. Meanwhile, the result for EFL learners’ perceptions toward MALL showed that the mean score was 54.93, which was equal with 78.55% of learners, and also could be categorized as positive perception. Therefore, the correlation between EFL learners’ perception toward MALL and their grade point achievement (GPA) was tabulated by using Spearman’s Rho formula. It was found that rvalue (0.315) higher than the rtable (0.1348), which indicated that the H0 was rejected and Ha was accepted. Thus, it was taken that there was a significant correlation between EFL learners’ perceptions toward MALL and learners’ GPA.